From Impartial Advocates to Political Agents: Role Switching and Trustworthiness in Consultancy - van Es, Robert (Journal of business ethics, 2002)
Consultancy firms inform, advise, implement and mediate in their own interests and in the interests of their clients. We can only guess if their work is also in the interest of the public. There is no critical and systematical assessment of the behavior of consultancy firms. What roles do consultancy firms chose? And what arguments do they use? In the nineties the international consultancy firm Hill & Knowlton took on two assignments that showed a remarkable difference in the required role the firm had to play. In the first role the firm acted as an impartial advocate, in the second role the firm acted as a political agent. An analysis of the argumentation for both roles shows us the familair short-sighted choice for the annual turnover at the cost of internal and external trustworthiness. In this decade consultancy firms will need to develop ethical assessments that meet more professional standards.